Unlocking the potential of CRISPR tools and databases for precision genome editing - Saraswat, Pooja; Ranjan, Rajiv (Frontiers in Plant Science, 2025)
Recent breakthroughs in CRISPR/Cas genome editing have transformed molecular biology research and offer significant potential across biotechnology and medicine. This has created a broad spectrum of computational tools and databases that aim to optimize each phase of the genome-edited workflow, from guide RNA design and off-target prediction through screening analysis and biological validation. Here, we survey major CRISPR tools and analyse their features in the context of precision genome editing. CRISPOR and CHOPCHOP versatile platform that provides robust guide RNA design for several species, integrated off-target scoring, and intuitive genomic locus visualization. This review gives an overview of these new resources that have been developed, grouped based on their functionalities like design of guide RNA, off-target predictions, genome-wide screens, and visualizations of the data. Furthermore, we discuss new trends in database development like their integration with genome browsers and implementation of machine learning. This review thus gives a useful overview of the dynamic field of CRISPR/Cas genome editing tools. It also serves as a helpful guide for researchers looking to utilize these tools in their research.